Complete Chloroplast Genome Sequence of Fortunella venosa (Champ. ex Benth.) C.C.Huang (Rutaceae): Comparative Analysis, Phylogenetic Relationships, and Robust Support for Its Status as an Independent Species - Ting Wang (Forests, 2021)
Fortunella venosa (Rutaceae) is an endangered species endemic to China and its taxonomic status has been controversial. The genus Fortunella contains a variety of important economic plants with high value in food, medicine, and ornamental. However, the placement of Genus Fortunella into Genus Citrus has led to controversy on its taxonomy and Systematics. In this present research, the Chloroplast genome of F. venosa was sequenced using the second-generation sequencing, and its structure and phylogenetic relationship analyzed. The results showed that the Chloroplast genome size of F. venosa was 160,265 bp, with a typical angiosperm four-part ring structure containing a large single copy region (LSC) (87,597 bp), a small single copy region (SSC) (18,732 bp), and a pair of inverted repeat regions (IRa\IRb) (26,968 bp each). There are 134 predicted genes in Chloroplast genome, including 89 protein-coding genes, 8 rRNAs, and 37 tRNAs. The GC-content of the whole Chloroplast genome was 43%, with the IR regions having a higher GC content than the LSC and the SSC regions. There were no rearrangements present in the Chloroplast genome; however, the IR regions showed obvious contraction and expansion. A total of 108 simple sequence repeats (SSRs) were present in the entire chloroplast genome and the nucleotide polymorphism was high in LSC and SSC. In addition, there is a preference for codon usage with the non-coding regions being more conserved than the coding regions. Phylogenetic analysis showed that species of Fortunella are nested in the genus of Citrus and the independent species status of F. venosa is supported robustly, which is significantly different from F. japonica. These findings will help in the development of DNA barcodes that can be useful in the study of the systematics and evolution of the genus Fortunella and the family Rutaceae.